2021
DOI: 10.3390/e23050623
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Deng Entropy and Extropy and Some Applications

Abstract: Deng entropy and extropy are two measures useful in the Dempster–Shafer evidence theory (DST) to study uncertainty, following the idea that extropy is the dual concept of entropy. In this paper, we present their fractional versions named fractional Deng entropy and extropy and compare them to other measures in the framework of DST. Here, we study the maximum for both of them and give several examples. Finally, we analyze a problem of classification in pattern recognition in order to highlight the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Some properties and extension of Deng entropy are discussed in [63]. More research can be found in [64][65][66].…”
Section: Deng Entropymentioning
confidence: 99%
“…Some properties and extension of Deng entropy are discussed in [63]. More research can be found in [64][65][66].…”
Section: Deng Entropymentioning
confidence: 99%
“…Proof By using the expressions of the cdf and the pdf of Y in terms of F X and f X obtained in (10), the weighted interval extropy of Y can be expressed as…”
Section: Remarkmentioning
confidence: 99%
“…Moreover, extropy is a measure better than entropy in some scenarios in statistical mechanics and thermodynamics [14]. More recently, some applications of extropy have been done in pattern recognition [3,10]. Qiu et al [19] defined the extropy for residual lifetime…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the work of [ 12 ] in which the concept of extropy was generalized to cumulative residual extropy, reference [ 13 ] investigated the properties of this term in both theoretical and applied aspects based on a version of the ranked set sampling. Moreover, Vaselabi et al, Buono and Longobardi, Kazemi et al [ 14 , 15 , 16 ] considered varextropy, Deng extropy, and fractional Deng extropy as generalizations of extropy. Furthermore, References [ 17 , 18 , 19 ] considered dynamic weighted extropy, the extropy of past lifetime distribution, and the extropy of k -records, respectively.…”
Section: Introductionmentioning
confidence: 99%